2021
DOI: 10.1177/03015742211004435
|View full text |Cite
|
Sign up to set email alerts
|

A Cephalometric Evaluation and Comparison of Skeletal, Dentoalveolar, and Soft Tissue Changes Brought about by the Forsus Fatigue Resistant Device and PowerScope Fixed Functional Appliance

Abstract: Background: Though studies have been conducted on the PowerScope, not many researches are available in the literature which compare its effects with other fixed functional appliances. Therefore, the aim of our study was cephalometric evaluation and comparison of the skeletal, dentoalveolar, and soft tissue changes brought about by the Forsus Fatigue Resistant Device and PowerScope appliance. Materials and Methods: Pre and Posttreatment cephalometric records of 20 patients with Class II Division 1 malocclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
6
4
0
Order By: Relevance
“…Regarding the maxillomandibular relationship, there was a statistically significant (P ≤ 0.05) decrease of ANB angle that accounted for the minimal improvement of the sagittal intermaxillary jaw relationship. This was agreed with the results of studies (11,14,16,17,19,23,24,28) using PowerScope appliance and studies (20,21,22) using MARA, FFRD, and TFBC appliances. While a study (29) using Eureka Spring found no statistically significant change in the ANB angle.…”
Section: Changes In the Skeletal Measurementssupporting
confidence: 90%
See 3 more Smart Citations
“…Regarding the maxillomandibular relationship, there was a statistically significant (P ≤ 0.05) decrease of ANB angle that accounted for the minimal improvement of the sagittal intermaxillary jaw relationship. This was agreed with the results of studies (11,14,16,17,19,23,24,28) using PowerScope appliance and studies (20,21,22) using MARA, FFRD, and TFBC appliances. While a study (29) using Eureka Spring found no statistically significant change in the ANB angle.…”
Section: Changes In the Skeletal Measurementssupporting
confidence: 90%
“…There was a statistically significant (P ≤ 0.05) retroclination of the upper incisor with the decrease in U1-SN, which agreed with the results of Powerscope studies (14,23,24,28) in addition to studies (25,26,21) using Churro Jumper, FNFS, JJ, and FFRD appliances. On the contrary, studies (11,19,16,17) using Powerscope˚ appliance and a study (22) using TFBC showed no change in the upper incisor inclination.…”
Section: Changes In the Dental Measurementssupporting
confidence: 86%
See 2 more Smart Citations
“…do not agree with Arora et al (14) and Nishanth et al (7) who reported non significance value of both measurements after using PowerScope appliance and in agreement with Kaur et al (15) and Shendy et al (16) who reported significant decrease in SNA angle and significant increase in SNB after using PowerScope appliance.…”
Section: Changes Within Each Groupmentioning
confidence: 57%